Study of thermal stabilization for polystyrene/carbon nanocomposites via TG/DSC techniques - Mansour, Sh A. (Springer, 2013)
The degradability and durability for polymer-nanocomposites under various environmental conditions are from the essential fields of research. This study was carried out to examine the thermal stability of polystyrene loaded by carbon (C) nanoparticles up to 20 wt% content. The thermal degradation of PS/C nanocomposites were studied by thermogravimetry analysis and differential scanning calorimetry (DSC) under non-isothermal condition and inert gas atmosphere at constant heating rate 10 A degrees C min(-1). The variation of degradation characteristic temperatures as a function of C content has been a non-monotonic behavior. The obtained results suggested that the C nanoparticles act as a promoter slowing down the degradation and providing a protective barrier to the nanocomposite, except 5 wt% C content. The latter exception was confirmed by DSC curve through the emergence of a small endothermic peak before the fundamental endothermic, melting, one.
Keywords: Nanocomposites; Polystyrene; Carbon nanoparticles; Thermal stability